Thematic chains - Rodrigues, Cilene (DELTA: Documentação e Estudos em Linguística Teórica e Aplicada, 2018)
Within the Principle & Parameters approach due mainly to proposals by Chomsky it has been argued that complex objects formed by movement (i.e., chains) are not eligible to participate in thematic relations. The present paper rejects this view, claiming that this restriction is justified neither on conceptual nor on empirical grounds.